Dampak dan Penanganan Penggunaan Gadget terhadap Perilaku Siswa Katolik di SMA Negeri 1 Hiliduho - Linda Nasran Waruwu; Sergius Lay; Paulinus Kanisius Ndoa (Journal New Light, 2024)
The development of communication technology in the current era of globalization is progressing very rapidly. The use of gadgets is currently very popular and needed by all groups, both children and parents, but gadgets themselves have several advantages and disadvantages, depending on each individual's use of the gadget. Everyone. In today's developments, gadgets are nothing new for users, especially students, and have even become their friends because they use them every day to help them find information or to help them with their assignments at school. The use of gadgets for students certainly has an impact on them, such as the positive impact of using gadgets being an effective and efficient learning tool for students, while the negative impact is apathy towards other people and the environment which influences daily behavior, sometimes using gadgets. Too much can affect and lead to bad things. Using gadgets is not wrong, but it makes it easier for us to interact with others if we use them for the right things. We as gadget users should be able to limit ourselves in using them so that we don't fall into bad things.